A case of autosomal recessive spinocerebellar ataxia type 18 with a novel mutation in GRID2 - Hetzelt, Katalin; Kraus, Cornelia; Kusnik, Stefan; Thiel, C.; Ekici, Arif Bülent; Reis, André; Zweier, Christiane (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

A case of severe autosomal recessive spinocerebellar ataxia type 18 with a novel nonsense variant in GRID2 - Hetzelt, Katalin; Kraus, Cornelia; Kusnik, Stefan; Thiel, Christian; Uebe, Steffen; Ekici, Arif Bülent; Trollmann, Regina; Reis, André; Zweier, Christiane (European Journal of Medical Genetics, 2020)
Autosomal-recessive spinocerebellar ataxia type 18 (SCAR18) is a rare neurologic disorder. It is caused by bi-allelic aberrations in the GRID2 gene, encoding an ionotropic glutamate receptor. In total, 20 affected individuals with mainly homozygous/compound heterozygous intragenic deletions/duplications, two different missense variants and one nonsense variant in GRID2 have been reported, so far. SCAR18 is characterized by delayed psychomotor development, intellectual disability, severely impaired gait due to cerebellar ataxia, ocular movement abnormalities, and cerebellar atrophy in brain imaging. By trio exome sequencing, we now identified a novel homozygous nonsense variant (c.568C > T; p.Gln190*) in GRID2 in a four year old female from a consanguineous family who presented with a particularly severe manifestation of SCAR18. The girl was born after an uneventful pregnancy and showed early-onset, profoundly delayed psychomotor development with no achieved psychomotor milestones at age 4 years. Additionally, she presented with severe muscular hypotonia, progressive truncal and appendicular ataxia, binocular vertical nystagmus, central hearing loss and incomplete loss of sight. She was dystrophic, interacted only very little and had behavioral anomalies such as eating hair and bruxism. Brain imaging showed cerebellar hypoplasia, extended cerebrospinal fluid spaces and beginning reduction of cerebral volume. Our findings further delineate the mutational and clinical spectrum of GRID2-associated spinocerebellar ataxia type 18 and indicate that homozygous nonsense variants are possibly associated with the severe end of the SCAR18 phenotypic spectrum.
CRIS-Team Scopus Importer:2020-07-31
Keywords: Ataxia; Autosomal-recessive; Cerebellar hypoplasia; GRID2; Psychomotor development; SCAR18

HRV-based Monitoring of Neonatal Seizures with Machine Learning - Lu, Hui; Kusnik, Stefan; Mammadova, Dilbar; Trollmann, Regina; Koelpin, Alexander (2024 46th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC), 2024)
With the rapid development of machine learning (ML) in biomedical signal processing, ML-based neonatal seizure detection using heart rate variability (HRV) parameters extracted from the electrocardiogram (ECG) has gained increasing interest. In this paper, we present a benchmarking of various ML classifiers for HRV-based neonatal seizure monitoring. We extract the HRV parameter in time-domain, frequency-domain, and nonlinear-domain from segments with duration ranging from 30 to 180 s and perform the feature selection with minimum redundancy and maximum relevance (mRmR). In the next step, we evaluate the performance using nested cross-validation on a dataset collected from 16 preterm and term newborns with neonatal seizures with a total duration of over 35 hours. The best-performing classifier was the support vector machine (SVM) with a linear kernel using HRV parameters from the 180 s segment, achieving an area under the operator characteristic operating curve (AUC) score of 0.627, 89.7% sensitivity, 34.6% specificity, and 92.3% good detection rate.
CRIS-Team Scopus Importer:2025-02-04
Keywords: ECG; HRV; machine learning; nested cross-validation; newborns; seizure monitoring

Phosphate Intoxication after Application of Enema - a Life-threatening Iatrogenic Complication - Marek, I.; Benz, Kerstin; Kusnik, Stefan; Morhart, P.; Botzenhardt, S.; Toni, I.; Rascher, Wolfgang (Klinische Pädiatrie, 2015)
Enemas are used in pediatric patients with constipation. Retention of phosphate containing enemas with prolonged resorption or reduced renal elimination of phosphate can result in life-threatening hyperphosphatemia with subsequent lethal hypocalcemia and acidosis.We report the case of a 6-month-old child who received phosphate-containing enema to treat acute aggravation of constipation. The used enema here was not licensed for this age group. Phosphate intoxication resulted (phosphate 19.87 mmol/l) and presented like a sepsis. Hyperphosphatemia was treated by hemodialysis. A non-diagnosed Hirschsprung disease had led to prolonged resorption of phosphate containing enema and to an ileus and toxic megacolon that had to be operated.Insufficient elimination of phosphate containing enema can result in lethal or life threatening hyperphosphatemia, hypocalcemia and metabolic acidosis. These can be treated efficaciously by hemodialysis. Because of the high risk of intoxication in using enemas containing phosphate in infants or in patients with gastrointestinal or renal comorbidities, physicians treating constipation should choose enemas without phosphate but with ingredients with lower risk like glycerol or sorbitol in this age group.
EVALuna2:18933